Small Scale Restoration Plan for the Issel River in Northwestern Germany - Buschmann, Silke (Arizona-Nevada Academy of Science, 2009)
From the Proceedings of the 2009 Meetings of the Hydrology Section - Arizona-Nevada Academy of Science - April 4, 2009, University of Arizona, Tucson, Arizona